2015
DOI: 10.1038/jcbfm.2014.256
|View full text |Cite
|
Sign up to set email alerts
|

Aging Impairs Myogenic Adaptation to Pulsatile Pressure in Mouse Cerebral Arteries

Abstract: Stability of myogenic tone in middle cerebral arteries (MCA) is essential for adequate control over penetration of pressure waves into the distal portion of the cerebral microcirculation. Because the increased pulse pressure observed in advanced aging is associated with cerebromicrovascular injury, the effect of aging on myogenic response of mouse MCAs was determined. Aging did not affect the myogenic constriction in response to static increases in pressure, whereas it significantly impaired pulsatile pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 16 publications
6
46
0
Order By: Relevance
“…The aforementioned functional adaptation of cerebral arteries to higher systemic blood pressure is believed to protect the cerebral microcirculation from pressure-induced injury (Toth et al 2013a;Toth et al 2014a). Our recent studies demonstrate that cerebral arteries of IGF-1 deficient mice do not exhibit a hypertension-induced adaptive increase in myogenic tone observed in mice with normal IGF-1 levels (Toth et al 2014a), which mimics the aging phenotype (Toth et al 2013a;Toth et al 2013c;Springo et al 2015). Pathological loss of autoregulatory protection in IGF-1 deficiency likely allows high blood pressure to penetrate the distal, injury-prone portion of the cerebral microcirculation, leading to significant downstream damage.…”
Section: Discussionmentioning
confidence: 85%
“…The aforementioned functional adaptation of cerebral arteries to higher systemic blood pressure is believed to protect the cerebral microcirculation from pressure-induced injury (Toth et al 2013a;Toth et al 2014a). Our recent studies demonstrate that cerebral arteries of IGF-1 deficient mice do not exhibit a hypertension-induced adaptive increase in myogenic tone observed in mice with normal IGF-1 levels (Toth et al 2014a), which mimics the aging phenotype (Toth et al 2013a;Toth et al 2013c;Springo et al 2015). Pathological loss of autoregulatory protection in IGF-1 deficiency likely allows high blood pressure to penetrate the distal, injury-prone portion of the cerebral microcirculation, leading to significant downstream damage.…”
Section: Discussionmentioning
confidence: 85%
“…However, it was apparent that the mature adult mice had a higher KD025 sensitivity and a higher active MT than the young and middle aged mice, respectively, which may at first seem counterintuitive. Nevertheless, previous studies have found an age-related decline in MT in both mesenteric arteries (Gros et al 2002) and middle cerebral arteries (Springo et al 2015) when comparing adult mice of 3-6 months of age with old mice at about 12-24 months of age. Thus, it seems that male mice at mature adulthood have a peak in their basal myogenic tone, which could be related to a lower estrogen-to-androgen ratio in this age group compared to younger as well as older male mice, and compared to age-matching female mice (Geary et al 2000a,b;Chan et al 2012).…”
Section: Role Of Rock2 and Aging In Myogenic Tonementioning
confidence: 78%
“…) and middle cerebral arteries (Springo et al. ) when comparing adult mice of 3–6 months of age with old mice at about 12–24 months of age. Thus, it seems that male mice at mature adulthood have a peak in their basal myogenic tone, which could be related to a lower estrogen‐to‐androgen ratio in this age group compared to younger as well as older male mice, and compared to age‐matching female mice (Geary et al.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely pathogenesis from SSRI usage seems to be the transient disturbance in the control of cerebrovascular tone. According to the proposed autoregulatory mechanism, the pressure-induced myogenic constriction of cerebral arteries by SSRI is one of the critical pathways along with cerebral microvascular circulation and calcium channel antagonist effects leading to smooth muscle calcium homeostasis [14][15][16]. Although RCVS and PRES have some overlapping features, with negative head and neck MRA it was excluded from the differential diagnosis, but RCVS has been reported in a patient presenting with serotonin syndrome [17].…”
Section: Discussionmentioning
confidence: 99%